Gambaran Kinerja Pendidik di Bimbingan Minat Baca dan Belajar (BIMBA) AIUEO Kota Padang - Elin Novianti; Syafruddin Wahid; Jalius Jalius (Universitas Negeri Padang, 2018)
This research is motivated by the success of institutions in developing the quality of tutoring institutions for early childhood (AUD). This study aims to describe the performance of educators which include (1) planning learning, (2) implementing learning, (3) assessing learning outcomes, (4) guiding and training students, (5) carrying out additional tasks. This study includes quantitative descriptive research, which describes the data as it is. The population consisted of fifty-four people and a sample of thirty-eight people was determined based on the sampling technique, namely cluster random sampling technique. Data collection tools using questionnaires and data analysis using percentage formulas. The results showed that, the performance of Bimba AIUEO educators in Padang was relatively high. This can be seen in the aspects of (1) planning learning, (2) implementing learning, (3) assessing learning outcomes, (4) guiding and training students, (5) carrying out additional tasks. Suggestions that all aspects of the educator's performance can be used by other educators.Keywords: Performance of Educators, Course and Training Institutions (LKP)